Agriculture in the Netherlands: Its recent past, current state and perspectives - van der Heide, C. Martijn; Silvis, Huib J.; Heijman, Wim J.M. (Applied Studies in Agribusiness and Commerce, 2010)
The driving forces that determine the prospects of the agricultural sector are dominated by international and European developments related to the demand for and supply of products. In this context, European policy, (such as the CAP), and national policy (e.g. nature management) can greatly influence the development of the agricultural sector.A further reduction of the support by the government forms an important element in the expected future developments.